2018
DOI: 10.1159/000492755
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Platelet-Rich Plasma on Peyronie’s Disease in Rat Model

Abstract: Purpose: The objective of this study was to evaluate the effects of intratunical injection of platelet rich plasma (PRP) for the treatment of Peyronie’s disease (PD) in a rat model. Materials and Methods: Twenty male Sprague-Dawley rats (300–350 g) were randomly divided into 4 groups: sham, PD, PD + PRP, and PRP. The PD + PRP groups received intratunical injections with 0.1 mL PRP on day 15 (treatment) or day 0 (PRP effect). Forty-five days following transforming growth factor-beta 1 injection, rats underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 28 publications
0
4
0
2
Order By: Relevance
“…Culha et al stated that PRP can produce PDlike plaques in animal models. 42 Our study is the first study showing the formation of PD-like plaque after PRP application in humans. Even though the PD-like plaque formation is small, it leads to discussing the safety of PRP application.…”
Section: Discussionmentioning
confidence: 70%
“…Culha et al stated that PRP can produce PDlike plaques in animal models. 42 Our study is the first study showing the formation of PD-like plaque after PRP application in humans. Even though the PD-like plaque formation is small, it leads to discussing the safety of PRP application.…”
Section: Discussionmentioning
confidence: 70%
“…It is a concentrate of several growth factors (PDGF, TGF-β, IGF, EGF, VEGF) prepared following centrifugation of the patient’s blood [ 8 ]. The effects of intratunic injection of PRP for the treatment of PD in rats by Culha et al [ 36 ] observed that PRP had no therapeutic effect on PD in the present study assessing the effects of PRP in the Peyronie model created with recombinant TGF-β1 injected into tunica albuginea of the rats.…”
Section: Discussionmentioning
confidence: 70%
“…It has been also shown to reduce the level of inflammatory mediators, while increasing the level of anti‐inflammatory mediators 22,23 . Regenerative and anti‐inflammatory effects of PRP have been demonstrated in various urological diseases such as erectile dysfunction, Peyronie's disease, and urethral stricture 24‐26 . Sekerci et al 11 examined, for the first time, the effect of PRP on I/R damage and hormone production in TT in the literature.…”
Section: Discussionmentioning
confidence: 99%